The predictive value of pre-treatment paroxysmal nocturnal hemoglobinuria clone on response to immunosuppressive therapy in patients with aplastic anemia: a meta-analysis. Issue 1 (1st January 2020) - Wang, Biao; He, Bai; Zhu, Yuan-dong; Wu, Wei
ABSTRACT: Background: Although pre-treatment paroxysmal nocturnal hemoglobinuria (PNH) clone has been reported in a fraction of aplastic anemia (AA) for a long time, its predictive value on response to immunosuppressive therapy (IST) remained debatable. Therefore, we conducted a meta-analysis to elaborate this issue. Methods: The identified articles were retrieved from five English databases PubMed, EMBASE, Web of Science, Medline, the Cochrane Library, and four Chinese databases Weipu, Wangfang, China National Knowledge Infrastructure (CNKI), and SinoMed. We extracted odds ratios (ORs) and the corresponding 95% confidential intervals (CIs) for response to IST in AA patients with pre-treatment PNH clone versus those without from the available studies. Results: Twelve studies covering 1787 patients were included this meta-analysis. The pooled ORs indicated that the pre-treatment PNH clone had no impact on 3-month response (pooled OR: 1.323, 95% CI: 0.260–6.735, p = 0.736), 6-month response (OR: 1.668, 95% CI: 0.802–3.470, p = 0.171), and overall response (OR: 2.220, 95% CI: 0.870–5.665, p = 0.095), including overall response in pediatric patients (OR: 1.919, 95% CI: 0.378–9.738, p = 0.432). However, pre-treatment PNH clone had a favorable impact on 12-month response (OR: 2.725, 95% CI: 1.525–4.870, p = 0.001). Conclusion: Pre-treatment PNH clone is associated with favorable 12-month response to IST in AA, the underlying mechanism needs further exploring.